Effects of pH change on the operation of electrolyzer and fuel cell - Ranjan A.; Singh A.; Kumar M. (My University, 2025)
Hydrogen has emerged as a new hope in the energy sector as it can meet all the short comings of fossil fuels and moves hand in hand with sustainable development idea. Over utilisation of fossil fuel has caused a great risk of global warming. As a result, 21st century has observed a rapid increase in fuel cell and hydrogen energy production. Generation of electricity with hydrogen and water, heat as bi products has supported this investment. All Fuel cell technologies, their design and operation is discussed in paper. Technologies are being developed for production of hydrogen in efficient way. Electrolyzer has been developed, which can convert water into hydrogen and oxygen. Electrolyzer along with their types and operation is discussed in paper. As hydrogen is the very heart of fuel cell operation, its performance will directly influence the fuel cell operation. It has been observed that electrolyzer operation can be affected by various means like change in pH during electrolysis of water and presence of air impurities. A small scale solar electrolyzer is operated in open green lush campus of IIT BHU to observe the impact of ph change and presence of air impurities. IIT BHU air quality test is done by ion chromatography. The above experimental observation put forward all the shortcomings of electrolyzer at small scale. The calculated data of paper provides an important idea for designing electrolyzer. The paper has covered all the major problem which can be faced by a large-scale system by analyzing its impact at small scale. The inference made in the paper can play a very crucial role in designing of the hydrogen fuel cell power generation system for commercial purpose. © 2020 IEEE.